Is the serum l-arginine level during early pregnancy a predictor of pregnancy-induced hypertension? - Wang, Jingwen (J Clin Biochem Nutr, 2015)
The objective of this study was to determine the concentration of serum l-arginine in healthy pregnant women and infant cord blood and to compare them with those in patients with pregnancy-induced hypertension (PIH). The serum concentration of l-arginine in normal pregnant women at early gestation (n = 186) was determined and analyzed based on maternal factors such as the age, pre-pregnancy body mass index (BMI), smoking and alcohol habits before pregnancy. Similarly, the concentration of cord blood of the newborns (n = 142) was also analyzed. These values were compared with those in the PIH group (n = 21). The potential risk factors for PIH were also estimated. The serum concentration of l-arginine at early gestation in normal pregnant women (88.65 ± 19.96 µM) was not affected by the maternal age and BMI before pregnancy. A lower l-arginine concentration at early gestation (<70 µM) significantly elevated PIH risk [adjusted odds ratio (OR) = 4.26, 95% CI 1.29–14.50]. In addition, either women with large body mass before pregnancy (BMI>25 kg/m(2)) or primipara women also showed a significant association with PIH risk [adjusted OR = 10.55 (2.95–40.68); 5.25 (1.72–19.15), respectively]. In conclusion, a lower l-arginine concentration at early gestation, overweight before pregnancy (BMI>25 kg/m(2)) and primipara could predict to the development of PIH.